Thrombomodulin's lectin-like domain reduces myocardial damage by interfering with HMGB1-mediated TLR2 signalling. (9th December 2013) - Herzog, Christine; Lorenz, Anika; Gillmann, Hans-Jörg; Chowdhury, Arpita; Larmann, Jan; Harendza, Thomas; Echtermeyer, Frank; Müller, Martin; Schmitz, Martina; Stypmann, Jörg; Seidler, Daniela G.; Damm, Martin; et al.
Abstract: Aims: Thrombomodulin (TM), via its lectin-like domain (LLD), exhibits anti-inflammatory properties partly by sequestering the pro-inflammatory cytokine, high-mobility group box 1 (HMGB1). Since myocardial damage after ischaemia and reperfusion is mediated by inflammation, we evaluated the cardioprotective effects of the LLD of TM. Using an in vivo mouse model of transient ischaemia and in vitro models of cardiomyocyte hypoxia, we assessed the ability of the LLD to suppress HMGB1-mediated activation of the receptors, receptor for advanced glycation endproducts (RAGEs) and Toll-like receptors (TLRs) 2 and 4. Methods and results: Thirty-minute myocardial ischaemia was induced in isoflurane-anaesthetized mice followed by 24 h of reperfusion in wild-type (WT) mice, in mice lacking the LLD of TM (TM LeD/LeD mice), and in WT with systemic overexpression of the LLD of TM induced by hydrodynamic transfection. Infarct size, HMGB1 protein, and apoptotic cells were significantly increased in TM LeD/LeD mice when compared with WT. Neonatal rat cardiomyocytes transfected with TLR2-, TLR4-, and RAGE-siRNA were exposed to hypoxia (0.8% O2 ) and reoxygenation (21% O2 ). HMGB1 augmented hypoxia-induced apoptosis in TLR2- but not in RAGE- or TLR4-suppressed cells. Administration of HMGB1- and TLR2-blocking antibodies in TM LeD/LeD mice prior to myocardial ischaemia diminished apoptosis. Therapeutic systemic gene therapy using the LLD reduced the infarct size and HMGB1 protein levels 24 h after reperfusion. Conclusion: The LLD of TM suppresses HMGB1-induced and TLR2-mediated myocardial reperfusion injury and apoptosis in vitro and in vivo .